Strategi Pegadaian Syariah Dalam Meningkatkan Jumlah Nasabah (Persero) Cabang Kuala Simpang - Siregar, Jamaluddin; Zainarti, Zainarti (LPPM Universitas Labuhanbatu, 2022)
This study will discuss the strategy of the Islamic financial industry in particular Shariah Pawnshop in increasing customers. Adjustment of appropriate strategies and techniques will greatly determine the sustainability of Shariah Pawnshop .Practice In industry Shariah pthere are actually many other financial services products that are developed in Shariah Pawnshop. The purpose of this study is to find out and analyze strategies of Shariah Pawnshop in dealing with the challenges of the industry at the present time. The method used is to use a literature study.